Black movements : performance and cultural politics - Colbert, Soyica Diggs, 1979- (Rutgers University Press, 2017)
"Black Movements analyzes how artists and activists of recent decades reference earlier freedom movements in order to imagine and produce a more expansive and inclusive democracy. Through an exploration of the way that black movements create circuits connecting people across space and time, Colbert offers important interventions into performance, literary, diaspora, and American studies"--